Alkylation and Ring Opening of Perfluoroalkyl- and Perfluoroaryl-Substituted 2-Siloxycyclopropanecarboxylates Yielding Fluorinated γ-Oxo Esters or β,γ-Unsaturated Ketones - Gladow, Daniel; Reissig, Hans-Ulrich (Synthesis, 2013)
Deprotonation of perfluoroalkyl- and perfluorophenyl-substituted methyl 2-siloxycyclopropanecarboxylates and subsequent reaction with alkyl halides furnished C-1 alkylated cyclopropanes with high diastereoselectivities. Smooth triethylamine trishydrofluoride mediated desilylation and ring opening afforded the corresponding γ-oxo esters in good to excellent yields. Treatment of methyl 2-siloxycyclopropanecarboxylates with Grignard reagents and subsequent ring opening in the presence of acid provided β,γ-unsaturated ketones with fluorine-containing substituents.
Keywords: donor–acceptor cyclopropanes; fluorine; γ-oxo esters; ring opening; defluorination